Answers

2014-08-09T23:27:00+08:00
If x₁ & x₂ are the roots of the quadratic equation  ax² +bx+c=0
then        x₁+x₂ =  -b/a          &  x₁x₂  =  c/a
to form the equation use this pattern
   x² - (sum of roots)x + (product of roots) =0
ex:  write a quadratic whose roots are  2 & -5
solution
x₁+x₂  =      2 + (-5)  = -3        sum of roots
x₁x₂      =      2*-5      -10         product of roots
so the equation is            x²+3x -10=0
note the change from negative to positive of the sum of roots sign





        



0